MicroRNA Signatures in Psoriatic Arthritis: From Pathogenesis to Precision Medicine - Ali, Zinah Abbass; Behayaa, Hiba Resheed; Abbas, Sheerin Hamza (Medical Science Journal for Advance Research, 2025)
Psoriatic arthritis (PsA) is a chronic inflammatory disorder caused by complex interactions among genetic, environmental, and epigenetic factors. MicroRNAs (miRNAs) have emerged as pivotal regulators of PsA pathogenesis by orchestrating synovial inflammation, osteoclastogenesis, immune dysregulation, and tissue remodeling. This review synthesizes the current evidence on dysregulated miRNA signatures in PsA, highlighting their dual roles as pathogenic mediators and diagnostic/therapeutic tools. Key upregulated miRNAs (e.g., miR-146a-5p, miR-21-5p, miR-221-3p, miR-941, and miR-130a-3p) amplify inflammation via NF-κB, IL-17/IL-23, and TNF-α pathways, while downregulated miRNAs (e.g., let-7b-5p, miR-30e-5p, miR-125b, and miR-125a-3p) disrupt protective checkpoints. Clinically, multi-miRNA serum panels (e.g., miR-221-3p/miR-130a-3p/miR-146a-5p/miR-151-5p/miR-26a-5p/miR-21-5p) achieve a high diagnostic accuracy (AUC >0.90), outperforming single biomarkers. Extracellular vesicle (EV)-encapsulated miRNAs enhance disease specificity and correlate with joint involvement. Therapeutically, miRNA levels predict treatment response (e.g., high miR-221-3p/miR-130a-3p levels associated with improved EULAR responses), and novel delivery systems (e.g., FNA-miR-125b) show efficacy in preclinical models. These findings suggest that miRNA signatures can be used as integrated tools for precision diagnosis, prognosis, and targeted therapy in PsA.